HNF6 and Rev-erbα integrate hepatic lipid metabolism by overlapping and distinct transcriptional mechanisms - Zhang, Yuxiang (Genes Dev, 2016)
Hepatocyte nuclear factor 6 (HNF6) is required for liver development, but its role in adult liver metabolism is not known. Here we show that deletion of HNF6 in livers of adult C57Bl/6 mice leads to hepatic steatosis in mice fed normal laboratory chow. Although HNF6 is known mainly as a transcriptional activator, hepatic loss of HNF6 up-regulated many lipogenic genes bound directly by HNF6. Many of these genes are targets of the circadian nuclear receptor Rev-erbα, and binding of Rev-erbα at these sites was lost when HNF6 was ablated in the liver. While HNF6 and Rev-erbα coordinately regulate hepatic lipid metabolism, each factor also affects additional gene sets independently. These findings highlight a novel mechanism of transcriptional repression by HNF6 and demonstrate how overlapping and distinct mechanisms of transcription factor function contribute to the integrated physiology of the liver.